Generating places of integration. A network model toward the skills assessment of foreign students - Bramanti, Donatella; Moscatelli, Matteo (International Journal about Parents in Education, 2023)
The study shows one or more models of network intervention, qualified as good practice, capable of generating places of integration between Italian and foreign students, with a specific reference to family engagement. We assessed the quality and sustainability of different partnership styles among the school, the public, the third sector and families, working on the assumption that this alliance is particularly appropriate in everyday life to achieve cultural integration between young Italians, foreigners and their families and to spread a network perspective able to successfully address the encounter among cultures. The research has studied 30 partnerships active in Lombardy Region, that has the largest number of foreign students in Italy, adding 3 cases out of Region and 3 projects conducted in other European countries (Feel, La Maleta intercultural, Rucksack). The study has identified specific guidelines to enable and support integrated networks between public or third sector and schools, capable of promoting and managing places of integration. Among the factors considered above there is the consistency and the structure of the network, the type and degree of collaboration between these actors, the type of governance put in place, the level of articulation of the relationship between the network and the socio cultural context in which it operates. Secondly we considered the project methodologies, the operation time, the extent of the catchment area, the level of the experience growth, the expansion of the partnerships. Also important were the methods of assessing the degree of social and cultural integration, educational and academic achievement in relation to skills, business integration, involvement of family background.